Cardiovascular Complication Induced by Cannabis Smoking: A Case Report - Hassen Ibn Hadj Amor; Imen Touil; Seif Boukriba; Skander Bouchnak; Salma Kraiem; Ramzi Rouabhia (Current Progress in Medicine and Medical Research Vol. 6, 2023)
This chapter present the first case of cannabis-induced spontaneous simultaneous double coronary and carotid dissection. The growing popularity of medical and recreational consumption of cannabis, especially among the youth, raises immediate concerns regarding its safety and long-terms effects. The cardiovascular effects of cannabis are not well known. Cannabis consumption has been shown to cause arrhythmia including ventricular tachycardia, and potentially sudden death, and to increase the risk of myocardial infarction. Although attention has focused on its neuropsychiatric effects, little has been given to cardiovascular side effects. Nevertheless, there are several case reports of vascular complications following cannabis use even in young people without cardiovascular risk factors. We describe the first instance of a cannabis user visiting the emergency room with an ischemic stroke coupled with an acute coronary syndrome caused by a spontaneous simultaneous double dissection of the carotid artery and the left anterior descending artery, with a successful outcome under medical care, in an effort to raise public awareness, particularly among young people, about the cardiovascular risks associated with cannabis use. This case shows the seriousness of complications due to the cannabis consumption, hence the need to limit or even prohibit its consumption. Given the legalisation of cannabis usage for recreational and medical purposes, which is spreading throughout many nations, a rise in such cases is to be anticipated.